Cropping systems as water harvesting techniques for barley production in arid and semi-arid areas in Jordan - Abu-Nukta, Ali; Sertyesilisik, Begum; Alkhaddar, Rafid (EMERALD GROUP PUBLISHING LTD, 2009)
Purpose - The purpose of this paper is to investigate the application of water harvesting techniques as a sustainability measure of the cropping system for barley production in the Fa'a farming area located in the Northern part of Jordan. Design/methodology/approach - Usually, the farmers plant barley to feed their animals. The climate of the area is semi-arid to arid. Annual average rainfall in the area is not enough for the survival of barley and farmers are usually grassing barley instead of harvesting. Overgrazing and mismanagement contribute to land degradation in the area, which affect the production system in the area. Findings - The paper investigates the runoff collection system which is framed with two different sizes in three different land uses: cultivated with barley; fallow and rangeland. Data are collected in all of five stormy events. The total soil sediment is measured for these land uses. The amount of water collected from runoff is also measured for the same areas. The ploughing against the slope with planting barley can reduce the runoff and soil sediment increasing soil moisture and reducing soil erosion. The barley production as biomass is highest using strip cropping as opposed to zero ratio control site or conventional cultivation. The plants' lengths were also higher in strip cropping ranging between 26 and 28 centimetres in the different strip cropping ratios compared to 23 centimetres in the conventional cropping system. Originality/value - By using the results from this new research to such an area, surface runoff from the uncultivated land can be used to supplement the rainfall to the cultivated land. This increases the share of runoff on the cultivated land to the degree where barley can be harvested.
Keywords: Crops; Rainfall; Water supply; Soil erosion; Jordan; Business & Economics